Pengaruh Ukuran Potongan Kopra dalam Proses Pengeringan - Gergorius Robertus Duyop; Yus Witdarko; Wahida Wahida (Musamus AE Featuring Journal, 2019)
Copra is the main raw material for making coconut oil. The quality of copra is very much determined by the drying process in order to achieve a water content level according to SNI. The purpose of this study was to determine the effect of the size of the copra pieces on reducing the moisture content in the drying process. The study was conducted in November 2018. There were three treatments in drying, namely coconut fruit pieces 1/2 part, 1/4 part, and 1/8 part. Drying is done under the sun for 42 hours in 6 days of drying. Measurement of the rate of reduction in copra water content was carried out at intervals of 1 hour. Water content was calculated using the gravimetric method. The results showed that the rate of reduction in water content in 1/8 part cut was faster than half or maupun part coconut. While the cut of ½ part and ¼ part, the rate of reduction in water content is not much different and does not show a significant difference. The final moisture content in drying copra for 1/2 part was 4.17%, copra 1/4 part was 4.11%, copra 1/8 part was 1.35%.